Our Neighbours, Ourselves. Contemporary Reflections on Survival - Bhabha, Homi K. (Hegel Lectures, 2011)
Homi K. Bhabha delivered the 2010 Hegel lecture, evoking the spirit of Hegel in an attempt to understand contemporary issues of ethical witness, historical memory and the rights and representations of minorities in the cultural sphere. Who is our neighbour today? What does hospitality mean for our times? Why is the recognition of others such an agonizing encounter with the alterity of the self?The lecture examplifies how the ?Third Space? - one of the key theories of Postcolonialism - helps us to establish a new understanding of cosmopolitanism and hospitality in a globalized world, based on the right of difference in equality.; Homi K. Bhabha,Harvard University, Cambridge, MA, USA.